2006
DOI: 10.1348/096317905x68213
|View full text |Cite
|
Sign up to set email alerts
|

In the wings of British orchestras: A multi‐episode interview study among symphony players

Abstract: An orchestral career has often been looked upon with awe by the public. A contract position with a well‐known orchestra is highly regarded, and often the target of competitive auditions. Yet, orchestral life‐style is easily misconceived by outsiders. Only a few researchers have been able to penetrate group barriers and gain the confidence of orchestra members, and none of these have reported emotions and cognitions pertinent to occupational development, career aspirations, vocational motivations and performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 23 publications
6
56
0
5
Order By: Relevance
“…Meanwhile, the most common topic in social science analyses of work and passion is entrepreneurship (e.g., Cardon et al, 2009). Among occupational groups that are mentioned as passionate are musicians (Brodsky, 2006) and professional football players (Bertrand, 2009). More ordinary employees are brought up in management literature, in which employer dreams of development of characteristics of workers that are supposed to enhance productivity, which has gone from work satisfaction over engagement in work to passion for work.…”
Section: Harmonymentioning
confidence: 99%
“…Meanwhile, the most common topic in social science analyses of work and passion is entrepreneurship (e.g., Cardon et al, 2009). Among occupational groups that are mentioned as passionate are musicians (Brodsky, 2006) and professional football players (Bertrand, 2009). More ordinary employees are brought up in management literature, in which employer dreams of development of characteristics of workers that are supposed to enhance productivity, which has gone from work satisfaction over engagement in work to passion for work.…”
Section: Harmonymentioning
confidence: 99%
“…6-Lectura precisa tocando con corrección desde la primera vez, aislando la dificultad, analizando su naturaleza y asumiendo un margen de aceptabilidad sin obsesionarse con la perfección. Bloomfield−Zeisler, 1913;Boehm, 1847;Brodsky, 2006;Bunting, 1999;Colomer, 1990;Coso,1992;Coyle, 2009;Dalia y Pozo, 2006;Dobson, 2010;Galamian, 1998;Goebl y Palmer, 2008;Jørgensen, 2004;Michalak, 2006;Neuhaus, 1987;Palmer y Drake, 1997;Ramos, 1981;Reid, 2006;Ruiz, Jabusch y Altenmüller, 2009;Stravinsky, 1977. 7-Práctica indirecta alterando el tempo de la interpretación, generando nuevos problemas por Altenmüller y Gruhn, 2002;Ballesteros, 2004;Barrie, 2007;Barry y McArthur, 1994;Bengtsson, Wanderley, 2009;Palmer y Hutchins, 2006;Papageorgiou, 2007;Parncutt, 2003;Reid, 2006;Stravinsky, 1977;Vines, Krumhansl, Wanderley y Levitin, 2006. 14-Visualización creativa, es decir, anteponer el pensamiento a la acción, pensar e imaginar antes de tocar. De esta estrategia, se derivan diversas propuestas; se puede efectuar la visualización creativa para adoptar un modelo corporal experimentado desde el interior (propiocepción), para crear una imagen cinestésica previa, para controlar mentalmente el movimiento (dirigir y supervisar) y para experimentar la receptividad sensorial interrelacionando un resultado positivo con sensaciones internas.…”
Section: Estrategia De Práctica Autoresunclassified
“…Bloomfield−Zeisler, 1913;Brodsky, 2006;Broughton, Stevens y Malloch, 2006;Chenoll, 1990;Colomer, 1990;Galamian, 1998;Grindea, 1991;Juslin, 2003;Miklaszewski, 1989;Neuhaus, 1987;Parncutt, 2003;Vines, Krumhansl, Wanderley y Levitin, 2006. 18-Efectuar una práctica de riesgo, por medio de una ejecución decidida y resuelta, comenzando firmemente y evitando detenciones durante el período de interpretación. Ballesteros, 2004;Chenoll, 1990;Cremaschi, 2012;Derbez, 2015;Galamian, 1998;Mateo, 1997;Neuhaus, 1987;Pin, 2001;Wrigley y Emmerson, 2013. 19-Práctica consciente en la que el foco de atención se sitúe en el presente de la ejecución, por medio de una percepción sensorial dedicada por completo a la actividad del momento interpretativo actual Bunting, 1999;Chenoll, 1990;Coso, 1992;Dalia y Pozo, 2006;Derbez, 2015;Oyan, 2006;Pérez Sánchez, 2003. 20-Uso de mensajes constructivos de auto-motivación para afianzar la confianza del propio intérprete, transformando su miedo en valentía y/o llevando a cabo un diálogo positivo consigo mismo.…”
Section: Estrategia De Práctica Autoresunclassified
“…Given that the symphony orchestra has provided a stable source of employment for thousands of musicians for more than 170 years (Brodsky 2006), it is perhaps not surprising that orchestral players are often the most fervent defenders of their traditions. These go back to the late 1800s, according to Boyle (2007); for example, most orchestral musicians still wear formal evening dress for concerts, and there is a strict hierarchy within the ensemble from conductor to rank and file or tutti players.…”
Section: Introductionmentioning
confidence: 99%
“…Boyle goes on to surmise that orchestral musicians perceive such traditions not only to be longstanding and universal but also an important component of what defines a worldclass symphony orchestra, and therefore Á along with the values and rituals that are passed down from one generation to the next Á the very identity of the professional classical musician. While orchestral musicians may defend their traditions, they nevertheless report low job satisfaction and high levels of stress attributable at least in part to their working conditions, over which they have little influence, and challenges to their integrity as artists (Allmendinger, Hackman, and Lehman 1996;Brodsky 2006;Hackman 2009;Parasuraman and Purohit 2000). Recent research supports these findings in so far as freelance orchestral musicians reported that, even though they experienced financial worries since their employment was insecure, they valued the opportunities denied to their colleagues in permanent orchestral posts to make their own decisions in relation to work (Dobson 2011).…”
Section: Introductionmentioning
confidence: 99%